Calculation of displacements and stresses in cylindrical shells by the boundary elements method - Aniskin, Aleksej (Array, 2018)
The application of the boundary element method to the calculation of a closed circular cylindrical shell of step-constant thickness, loaded over the entire surface by a uniform normal pressure, is described. The numerical example is considered. The results of the calculation are compared by two numerical methods – boundary and finite elements.